Targeting Vision: Insights into the Genetics of Inherited Retinal Diseases in Ireland - Kopčić, Ella (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2026)
Inherited retinal diseases (IRDs) represent a clinically and genetically heterogenous group of disorders, and are the leading cause of blindness worldwide in adults of working age. The Target 5000 project was set up in collaboration with clinicians, ophthalmologists, researchers and patient groups, with the goal of providing comprehensive genetic diagnoses to the IRD population of Ireland and establishing an IRD care pathway. This thesis broadly explores the use of next generation sequencing (NGS) technologies in genetically diagnosing IRDs in the Irish Target 5000 cohort, focusing on variant identification, prioritisation, classification and functional studies. The landscape study presented within describes the use of single molecule Molecular Inversion Probes (smMIPs) as a form of targeted panel sequencing to analyse a cohort of 223 Irish patients presenting with an inherited macular dystrophy (iMD). This study provides the first overview of the genetic architecture of iMD in Ireland, enabling the identification and interpretation of 9 novel candidate disease-causing variants and a solve rate of 33%, with 72 patients considered to be genetically resolved. Novel variants, such as a splice-altering variant in ABCA4 and a large 8kb deletion within CDH3 have been investigated using in vitro functional assays and breakpoint analyses. In addition, the first BBS7 pedigree reported in Ireland is described. Cascade analyses undertaken as part of Target 5000 are examined, providing additional perspectives on the complexities of IRDs as clinically and genetically heterogeneous disorders. Instances of variable penetrance and hypomorphic alleles are discussed, along with the classification of further novel IRD variants utilising in silico tools and population data, as well as segregation and allelic information to predict pathogenicity. In vitro functional assays were undertaken to deepen our understanding of the mechanism of disease, allowing for in depth variant classifications creating a clearer genetic diagnosis for affected patients. Among variants assayed, a coding variant in RPGR was analysed and found to be the first variant identified in an IRD gene that leads to the creation of a branchpoint motif within an exon. Overall, this research demonstrates that targeted panel sequencing, complemented by thorough variant classification and functional assays represents an effective form of preliminary sequencing. Genomic testing can provide many benefits to IRD patients such as clarity on disease progression and prognosis, potential eligibility for emerging clinical trials and gene therapies, access to a multidisciplinary teams and family planning, risk assessment services and genetic counselling. Continued landscape sequencing studies, such as those presented within this thesis, will indeed expand our knowledge of the mechanism of disease and functionality of disease variants in IRDs, as well as contributing to the global repertoire of variants identified in IRD genes.
APPROVED
Keywords: Inherited Retinal Disease (IRD); NGS technologies; Functional assays; Retina; Human Genetics; Targeted panel sequencing; Ocular genetics; Variant classification; DNA sequencing; Splicing; Macular dystrophy; smMIPs panel sequencing